Multipliers type I and II of production and employment in tourism in Peru, 2015-2020 - Tello, Mario D. (2024)
Based on the Tourism Satellite Accounts from 2015 to 2020 (MINCETUR 2021 and 2022), this work estimates the Type I and Type II multipliers of tourism in Peru for the years 2015, 2019 and 2020. The methodology, based on input matrices -product, indicates that the Type I and II multipliers are determined by: technology (through the technical coefficients of the input-product matrix; the linkages between the tourism sectors and the rest of the sectors; and the participation in production, added value, employment of tourism sectors of the equivalents for the economy; and of household demand or consumption. The most notable result of the estimates for the 2015-2020 period is that the orders of magnitude of the tourist complex multipliers have. been similar, those of Type I and those of Type II, implying that the fall in employment and tourism GDP in 2020 is due in part to the drastic fall in tourism demand. Tourism demand decreased in the contribution to the GDP of the economy. from 7% in 2019 to 2.5% in 2020.